Use of duration and rise time cues in the labelling of affricate and fricative speech sounds by children with reading difficulties. (30th December 2020) - Antony Hughes, J.; Tree, Jeremy; Reed, Phil
Abstract : Differentiation of speech is predictable from abilities to discriminate the speed at which a sound reaches its optimum amplitude (rise time). This study investigated whether rise time identification of an affricate–fricative continuum would be impacted upon by dyslexia. Children between 10 and 14 years old identified sounds along a continuum of fricative to affricate sounds (cha–sha continuum), using a novel automated learning rise time identification task. Those with higher dyslexia likelihoods (measured by the Dyslexia Screening Test – Secondary), and poor reading scores (measured by the British Abilities Scales), showed a difference in rise time identification; greater distances between rise times were needed for those with a high risk of dyslexia to recognise fricative–affricate differences than for controls. These results were not impacted upon by IQ scores.